Preparation and Investigation of Hybrid Periodic Structures Based on Perovskite-Like Materials - L. A. Bliznyuk; T. P. Petrochenko; A. K. Letko; V. I. Kasko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
Syntheses and investigations of bulk samples of compositions based on BaxSr(1–x)TiO3, Pb(Zr,  Ti)O3, Bi1,7Pb0,3Sr2Ca(n–1)CunO(n+4+1),  n  =  (5, 9, 12), which are used to obtain hybrid structures, have been carried out. The technology for producing high temperature superconductor–ferroelectric hybrid structures has been developed and the optimal temperature-time modes for their production have been determined. The conditions for the formation of the high temperature superconductor–ferroelectric structure have been studied. The microstructure, crystal structure and electrical properties of the high temperature superconductor–ferroelectric hybrid structure were studied. The ferroelectric–superconductor transition boundary was studied and it was found that its size is 4 μm. The ferroelectric–superconductor–electrode structures have been formed. It has been shown that the deposition of  silver contacts on the surface of a superconducting coating is possible in one technological cycle. It has been established that to obtain composite materials with high electrical parameters it is necessary to use superconducting materials Bi1,7Pb0,3Sr2Ca(n–1)CunOy с n ≥ 12.